Seropositivity of Toxoplasmosis in Antenatal Women with Bad Obstetric History in a Tertiary-care Hospital of Andhra Pradesh, India - Sarkar, Munmun Das; Anuradha, B; Sharma, Neelam; Roy, Rabindra Nath (Journal of Health, Population and Nutrition, 2012)
Toxoplasmosis is a well-documented cause of bad obstetric history (BOH) and a major reason of congenitally- acquired infection. The study was conducted to determine the seropositivity of toxoplasmosis in women with BOH, attending the antenatal clinic of the Mamata General Hospital, Khammam, Andhra Pradesh, India. The study subjects included 105 antenatal women with BOH and 105 antenatal women who had previous normal deliveries. A serological evaluation was carried out to determine the presence of Toxoplasma gondii-specific IgG and IgM antibodies, using commercial diagnostic kits, by the enzyme-linked immunosorbent assay method. The seropositivity for Toxoplasma was 49.52% in the study group compared to 12.38% in the control group. The difference in seropositivity was significant (p=0.00). The seroprevalence gradually increased with advancing age. Abortion (51.92%) was the commonest form of pregnancy wastage, followed by stillbirths (36.53%) and premature deliveries (7.69%). The seropositivity of toxoplasmosis was significantly higher in the study group than that in the control group, and the seropositivity played an important role in determining the foetal outcome. Considering the subclinical pattern of infection, routine serological test is recommended for all pregnant women for both IgG and IgM antibodies DOI: http://dx.doi.org/10.3329/jhpn.v30i1.11287 J HEALTH POPUL NUTR 2012 Mar;30(1):87-92